Real‐world effectiveness and safety of apremilast in psoriasis at 52 weeks: a retrospective, observational, multicentre study by the Spanish Psoriasis Group. (17th June 2020) - del Alcázar, E.; Suárez‐Pérez, J.A.; Armesto, S.; Rivera, R.; Herrera‐Acosta, E.; Herranz, P.; Martín, I.; Montesinos, E.; Hospital, M.; Vilarrasa, E.; Ferran, M.; Ruiz‐Villaverde, R.; et al.
Abstract: Background: Little has been published on the real‐world effectiveness and safety of apremilast in psoriasis. Objectives: To evaluate the effectiveness, safety and drug survival of apremilast at 52 weeks in patients with moderate to severe plaque psoriasis or palmoplantar psoriasis in routine clinical practice. Methods: Retrospective, multicentre study of adult patients with moderate to severe plaque psoriasis or palmoplantar psoriasis treated with apremilast from March 2016 to March 2018. Results: We studied 292 patients with plaque psoriasis and 85 patients with palmoplantar psoriasis. The mean (SD) Psoriasis Area and Severity Index (PASI) score was 10.7 (7.0) at baseline and 3.0 (4.2) at 52 weeks. After 12 months of treatment, 73.6% of patients had a PASI score of 3 or less. In terms of relative improvement by week 52, 49.7% of patients achieved PASI‐75 (≥75% reduction in PASI score) and 26.5% achieved PASI‐90. The mean physician global assessment score for palmoplantar psoriasis fell from 4.2 (5.2) at baseline to 1.3 (1.3) at week 52. Overall drug survival after 1 year of treatment with apremilast was 54.9 %. The main reasons for treatment discontinuation were loss of efficacy (23.9%) and adverse events (15.9%). Almost half of the patients in our series (47%) experienced at least one adverse event. The most common events were gastrointestinal problems. Conclusions: Apremilast may be a suitable alternative for the treatment of moderate to severe psoriasis and palmoplantar psoriasis. Although the drug has a good safety profile, adverse gastrointestinal effects are common.